A handbook on anti-dumping investigations - Czako, Judith (Cambridge University Press, 2003)
The focus of growing concern in international trade policy, anti-dumping procedures have become a source of tension between countries. This handbook covers major areas arising in anti-dumping investigations as embodied in the relevant World Trade Organization (WTO) provisions and offers well-sourced information and guidance for understanding the intricacies of these proceedings. The volume will assist investigators conducting the required studies; government officials; and professionals working in importing and exporting enterprises, as well as scholars concerned with international trade issues.